Batman's Batman : A Memoir from Hollywood, Land of Bilk and Money - Uslan, Michael, 1951- (Book collections on Project MUSE., 2022)
All good stories deserve a sequel. Batman's Batman is the sequal to Michael E. Uslan's memior, The Boy Who Loved Batman. It offers an insider's look at Hollywood and the process of how movies and television shows go from the drawing board to your screens.